2018
DOI: 10.1089/neu.2017.5049
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Acute Traumatic Brain Injury by Circulating Extracellular Vesicles

Abstract: Inflammatory lesions in the brain activate a systemic acute-phase response (APR), which is dependent on the release of extracellular vesicles (EVs) into the circulation. The resulting APR is responsible for regulating leukocyte mobilization and subsequent recruitment to the brain. Factors that either exacerbate or inhibit the APR will also exacerbate or inhibit central nervous system (CNS) inflammation as a consequence and have the potential to influence ongoing secondary damage. Here, we were interested to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…Noteworthy, EVs also play critical roles in TBI ( 132 ). Similar to other injuries, cell–cell communication is critical for regulating the immune response in TBI ( 133 ).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Noteworthy, EVs also play critical roles in TBI ( 132 ). Similar to other injuries, cell–cell communication is critical for regulating the immune response in TBI ( 133 ).…”
Section: Clinical Relevancementioning
confidence: 99%
“…In fact, Kurachi et al showed that EVs derived from various ECs (aortic, brain, umbilical) have similar effects on oligodendrocytes [ 63 ], which suggests potential similarities among EVs from different vascular beds in executing some actions. Although cross-talk between the vascular lineages has not been examined, it has been demonstrated by adoptive transfer of BMEC-derived EVs (in vivo) that these vesicles can have an effect on other organ systems such as the liver [ 64 , 65 ].…”
Section: Ec-derived Evs: Role In Cns Pathologymentioning
confidence: 99%
“…The latter include activation of inflammatory cytokines, chemokines, and micro-RNAs (miRs) (Perry et al, 2010;Prinz and Priller, 2014). Activated microglia also release extracellular vesicles (EVs), including microparticles (MP; also called microvesicles) and exosomes containing pro-inflammatory molecules, which can further enhance and potentially propagate the inflammatory response after TBI (Hazelton et al, 2018;Paolicelli et al, 2018). Several in vitro and in vivo models, including lipopolysaccharide (LPS)-treated primary microglia, cell lines (e.g., BV2 microglia), and LPS-challenged mice have been used to mimic such neurotoxic microglial activation (Loane et al, 2009;Mao et al, 2012;Fenn et al, 2014;Yuan et al, 2015;Hung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%